Fitonematoides na cultura da cana-de-açúcar no Rio Grande do Sul: levantamento, caracterização e reação de genótipos a Meloidogyne javanica e Pratylenchus zeae - Bellé, Cristiano (2014)
The objectives of this study were to characterize root-knot and lesion nematode populations of sugar cane fields of the Rio Grande do Sul state, and to evaluate the reaction of sugar cane genotypes to Meloidogyne javanica and Pratylenchus zeae. The Meloidogyne spp. populations were characterized biochemically by esterase (Est), and morphologically by the configuration of perineal region of females. The Pratylenchus populations were identified by morphological and morphometric characters. Subsequently, the reaction of ten sugar cane cultivars to M. javanica and P. zeae was evaluated at greenhouse conditions. Ninety Meloidogyne sp. populations were detected of in 67.17% of collected samples and 12 esterastic phenotypes (Est) were identified. Among the root-knot nematode populations purified and identified, 32 of them presented the Est J3 phenotype (Rm: 1.00; 1.24; 1.40), 51 populations, Est J2 (Rm: 1.00; 1.23), and four populations the phenotype Est J2a (Rm : 1.00; 1.40), typical of M. javanica, that corresponded to 19.75%, 31.48% and 2.47% of the samples, respectively. Four populations of M. incognita Est I1 (Rm: 1.02), and 25 of M. incognita Est I2 (Rm: 1.02; 1:09) phenotypes, corresponding to 2.47% and 15.43% of Meloidogyne spp. samples, respectively, were also detected and identified. In addition, 12 populations were identified as M. arenaria Est A2 (Rm: 1.26, 1.32), three populations of M. ethiopica Est E3 (Rm: Rm: 0.92; 1.15; 1.32), three of M. hapla Est. H1 (Rm: 1.17), and just one of M. luci (Rm: 1.00; 1.16; 1.34), corresponding to 7.41, 1.85, 1.85 and 0.62% of the root-knot nematode populations, respectively. Among the atypical species detected in this study, six populations of Meloidogyne sp.1 were identified with the phenotype Est Sc 1 (Rm: 0.86; 0.94), 12 Meloidogyne sp.2 as Est Sc 2 (Rm: 1.05; 1.29), and nine Meloidogyne sp.3 as Est A1 (Rm: 1.26), corresponding to 4.47, 9.05, and 6.71% of the root-knot nematodepopulations, respectively. However, by the perineal configurations, these populations could not be identified. Pratylenchus spp. was detectedin 98,8% of the collected samples. In the samples morphologica and morphometrically characterized to species of Pratylenchus, 51 populations were identified as P. zeae (84.61%) and 23 populations as P. brachyurus (35.38%). Evaluating the resistance reaction of sugar cane genotypes to both nematodes, although M. javanica and P. zeae have showed FR> 1.00 for all tested genetic materials, it was verified different levels of susceptibility. However, lower M. javanica reproduction was observed in RB008347, RB877935, RB975944, and 'RB987932; and either for P. zeae in RB987932 and RB966928 genotypes.